Matarumah Parentah Dalam Sistem Pemerintahan Adat Di Maluku - Dokolamo, Hamid (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2020)
Traditional governance and its institutions in Maluku began to disappear and erode during Indonesia's New Order era when the government implemented Law No. 5 of 1979, which standardized the village governance system across the country. However, with the advent of the era of autonomy and the enactment of laws allowing each region to restore its traditional governance systems, the people and regional government of Maluku began to apply these laws. The Provincial Government of Maluku issued Regional Regulation No. 14 of 2005, allowing each regency and city to restore the traditional governance system in each village (negeri). Nevertheless, controversy has arisen over the position of Matarumah Parentah, or the right to serve as the head of the village government. Almost every negeri (village) that has returned to traditional governance faces issues regarding which matarumah (lineage house) has the right to occupy the village head or raja position. Therefore, to maintain social harmony, customs, and the historical leadership of the Negeri, the residents need to restore the government leadership to the Matarumah Parentah as the legitimate authority. Adherence to and respect for tradition are crucial in maintaining harmony and integrity among the residents. The people of Maluku must recognize the importance of traditional governance, passed down by their ancestors to the current generation, and must observe and implement it faithfully. Tradition, as a means of conflict resolution and tension control within the community, must serve as a guiding principle for the residents of the Negeri.